Induction of TDO2 and IDO2 in Liver by High-Fat Feeding in Mice: Discrepancies with Human Obesity. (January 2013) - Poulain-Godefroy, Odile; Eury, Elodie; Leloire, Audrey; Hennart, Benjamin; Guillemin, Gilles J.; Allorge, Delphine; Froguel, Philippe
Low-grade and chronic inflammation is elicited in white adipose tissue in human obesity. The presence of inflammatory molecules leads to an increased tryptophan catabolism through the induction of indoleamine-2, 3-dioxygenase-1 (IDO1). In order to characterize the mechanisms underlying this dysregulation, we have studied 2 mouse models of obesity. Unexpectedly, we did not detect any IDO1 expression in obese or lean mice adipose tissue. In a previous study, we did not find any significant difference in the liver for IDO2 and tryptophan-2, 3-dioxygenase (TDO2) gene expression between normal weight and obese patients. IDO2 and TDO2 expression was increased in the liver of high-fat fed mice, but not in ob/ob mice, and was strongly correlated with hydroxysteroid-(11-beta) dehydrogenase-1 (HSD11B1) expression, an enzyme that generates active cortisol within tissues. In conclusion, despite a dysregulation of tryptophan metabolism, obese mice display discrepancies with human obesity metabolism, rendering them inappropriate for further investigations in this animal model.